Breastfeeding Trends and it's Related Factors in Indonesia: A National Survey - Prasetyo, Yoyok Bekti; Rahayu, Henik Tri; Kurnia, Anggraini Dwi; Masruroh, Nur Lailatul; Melizza, Nur; Latif, Rusnani AB (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This cross-sectional study aimed to examine breastfeeding trends and factors in Indonesia using Demographic Health Survey (DHS) data from 2007 to 2017. The research data were obtained from three Indonesia Demographic Health Surveys. The data covered households and women aged 15‒49 years old, including 40,701 households and 32,895 women in 2007; 43,852 households and 45,607 women in 2012; and 47,963 households and 49,627 women in 2017. Descriptive statistics was deployed to analyze the sociodemographic factors of the respondents. A questionnaire was employed to obtain data on the mothers' age, residence, education, economic status, mother working, marital status, literacy, place of delivery, first Antenatal Care (ANC) place, child size at birth, and gender of the child. Multinomial logistic regression analysis was used to analyze factors related to breastfeeding and how big the impact is. The findings indicate that the trend of breastfeeding in Indonesia significantly decreased based on the characteristics of mothers and children. The rates of breastfeeding (exclusive breastfeeding infants aged 0‒5 months who received only breast milk) among mothers living in urban areas decreased significantly from 41.6% in 2012 to 38.4% in 2017. In 2017, children with normal birth weight (OR=0.87, 95% CI:0.53‒1.45), boys (OR=1.01, 95% CI:0.92‒1.10), and non-illiterate mothers (OR=0.50, 95% CI:0.46‒0.55) had higher odds of breastfeeding compared to children with small birth weight, girls, and illiterate mothers. Factors associated with breastfeeding also change every year. In 2012, breastfeeding was related to marital status and delivery, but in 2017 it was not associated with those factors. Factors related to breastfeeding in Indonesia are age, residence, education, weight index, size of child at birth, mother’s occupation, marital status, literacy, place of delivery, and first ANC place. These results are important for developing policies to improve maternal and child health in Indonesia by increasing education and mother training for early initiation of breastfeeding.